2016
DOI: 10.1124/jpet.115.229799
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostaglandin D2 and DP1 Receptor on Japanese Cedar Pollen-Induced Allergic Rhinitis in Mice

Abstract: Although we previously demonstrated the contribution of the DP 1 receptor in nasal obstruction using animals sensitized with ovalbumin in the presence of adjuvant, the contribution of the DP 1 receptor in sneezing is unclear. Here, we developed a mouse model of Japanese cedar (JC: Cryptomeria japonica) pollinosis to evaluate the symptoms of sneezing. To achieve this, we used JC pollen crude extract in the absence of adjuvant to sensitize mice to develop a model closer to the pathophysiology of human JC pollino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While DP 1 agonist increased allergen-induced sneezing compared to placebo in a model of Japanese cedar pollen-induced allergic rhinitis, this endpoint was reduced in DP 1 knockout mice compared to WT mice. (Nakano et al, 2016) These investigators also reported a DP 1 antagonist completely inhibited PGD 2 -induced augmentation of electrical and histamine-induced excitability of trigeminal ganglion excitability in guinea pigs. (Nagira et al, 2016) Allergen sensitized and challenged DP 1 KO mice had significantly inhibited airway responsiveness and BAL concentrations of IL-4, IL-5, and IL-13 compared to WT mice, while there was no difference in the BAL levels of IFN-γ.…”
Section: Individual Pgsmentioning
confidence: 93%
“…While DP 1 agonist increased allergen-induced sneezing compared to placebo in a model of Japanese cedar pollen-induced allergic rhinitis, this endpoint was reduced in DP 1 knockout mice compared to WT mice. (Nakano et al, 2016) These investigators also reported a DP 1 antagonist completely inhibited PGD 2 -induced augmentation of electrical and histamine-induced excitability of trigeminal ganglion excitability in guinea pigs. (Nagira et al, 2016) Allergen sensitized and challenged DP 1 KO mice had significantly inhibited airway responsiveness and BAL concentrations of IL-4, IL-5, and IL-13 compared to WT mice, while there was no difference in the BAL levels of IFN-γ.…”
Section: Individual Pgsmentioning
confidence: 93%
“…In modeling, 10 µl of 3 mg/ml pollen extract in PBS is intranasally administered on days 0 and this is repeated on day 7,14,21,22,23,24,27,28,29, and 30 ( Figure 7). Pollen extract Administration should be done without anesthesia to stop pollen extract reaching to the lower airways (64)(65)(66)(67). Administration methods are shown in Figure 8.…”
Section: Pollen Allergic Rhinitis Modelmentioning
confidence: 99%
“…However, PGD 2 is most known for its pro-inflammatory properties in a variety of pathologies. Notably, it exacerbates adjuvant induced joint inflammation (Tsubosaka et al, 2014), allergic rhinitis (Nakano et al, 2016), Crohn's disease (Le Loupp et al, 2015;Radnai et al, 2016), and mast cell-induced vitreoretinopathy (Kuo et al, 2015). It also plays a role in depression-related behavior (Onaka et al, 2015) and in pain, being implicated in esophageal nociception (Zhang et al, 2013a), migraine (Antonova et al, 2013), and neuropathic spinal pain (Kanda et al, 2013).…”
Section: Prostaglandinsmentioning
confidence: 99%